Metastatic Renal Cell Carcinoma to the Parotid Gland in the Setting of Chronic Lymphocytic Leukemia - Robert Deeb; Ziying Zhang; Tamer Ghanem (Case Reports in Medicine)
Renal cell carcinoma (RCC) is infamous for its unpredictable behavior and metastatic potential. We report a case of a patient with a complex history of multifocal renal cell carcinoma and chronic lymphocytic leukemia (CLL), who subsequently developed a parotid mass. Total parotidectomy revealed this mass to be an additional site of metastasis which had developed 19 years after his initial diagnosis of RCC.